Implementasi Media Pembelajaran Mobile Learning Berbasis Android Pada Mata Kuliah Sejarah Australia dan Oceania untuk Meningkatkan Literasi Historis Mahasiswa - Valensy Rachmedita; Nur Indah Lestari; Aprilia Triaristina; Yustina Sri Ekwandari; Ema Agustina (Universitas Galuh, 2026)
This study aims to analyze the effectiveness of Android-based mobile learning media in improving students’ digital-based historical literacy in the Australian and Oceanian History course at the University of Lampung. The research employed a quasi-experimental method using a One Group Pretest–Posttest Design involving 56 students of the History Education Study Program, cohort of 2023. Data were collected through a digital-based historical literacy test covering students’ abilities to understand historical contexts, analyze digital historical sources, interpret the meaning of historical events, and utilize digital technology to obtain and process historical information. The results indicate a significant improvement in students’ historical literacy after the implementation of Android-based learning media. The average pretest score of 73.12 increased to 83.75 in the posttest, with a difference of 10.63 points. The results of the Paired Sample t-Test show a Sig. (2-tailed) value of 0.000 < 0.05, indicating a statistically significant difference before and after the treatment. Android-based mobile learning media were proven effective in enhancing students’ critical thinking skills, digital-based historical literacy, and learning independence. These findings imply that the utilization of Android-based learning media can serve as an innovative approach to history learning that is interactive, flexible, and adaptive to students’ characteristics in the digital era.